Registrasi Ulang Identitas Kendaraan Bermotor akibat Ketidaksesuaian Nomor Mesin: Analisis Normatif atas Kekosongan Regulasi dan Perlindungan Hukum Pemilik Kendaraan - Satria Kalindra Imam Pradhata (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The crankcase is a structural engine component that bears the engine number as an official vehicle identity marker. When a crankcase suffers irreparable structural damage—caused by accidents, lubrication failure, corrosion, or manufacturing defect—its replacement automatically creates a discrepancy between the vehicle's physical engine number and the data recorded in official registration documents (STNK/BPKB). This discrepancy carries serious legal consequences yet lacks a sufficiently clear resolution framework under current regulations. This study examines two issues: (1) the registration requirements for replacing an engine number following crankcase damage; and (2) the legal remedies available when the replacement is performed by an unlicensed workshop. Employing normative legal research with statutory and conceptual approaches, the study identifies that Law No. 22 of 2009, Government Regulation No. 55 of 2012, and National Police Regulation No. 7 of 2021 do not specifically distinguish between an engine number change caused by component damage and a full engine replacement, thereby creating a regulatory gap (regeling vacuum) with disparate practical outcomes. The novelty of this study lies in constructing the concept of alternative material evidence (vrij bewijs) as a substitute mechanism when a licensed workshop certificate is unavailable, and in rejecting the doctrine of administrative responsibility transfer from the unlicensed workshop to the vehicle owner.